"Diversity Is Important to Me": White Parents and Exposure-to-Diversity Parenting Practices. Issue 4 (October 2019) - Underhill, Megan R.
Drawing upon interviews with 40 parents in Cincinnati, Ohio, the author explores how "exposure to diversity, " an implicit racial socialization practice, has become a defining feature of how some middle-class white parents teach their children about race and reflect on what it means to be a good white parent. Exposure to diversity involves white parents' active efforts to expose their children to people of color via trips to multiracial parks, enrollment in multiracial schools, or residence in multiracial neighborhoods. The author argues that white parents' efforts are informed by their adherence to both a "diversity ideology" wherein racial diversity is frequently, but not always, framed as a positive social dynamic that enriches their family's white life, and a middle-class desire to craft a high-status white child via distinction-oriented parenting practices. Taken together, white middle-class parents pursue an exposure-to-diversity strategy because they believe, whether consciously or not, that diversity provides them and their children with the means to facilitate small-scale social change and to craft a comfortable, open-minded white child who possesses racial and class distinction.